2006
DOI: 10.1038/sj.onc.1209353
|View full text |Cite
|
Sign up to set email alerts
|

The human homologue of the RNA polymerase II-associated factor 1 (hPaf1), localized on the 19q13 amplicon, is associated with tumorigenesis

Abstract: The 19q13 amplicon in pancreatic cancer cells contains a novel pancreatic differentiation 2 (PD2) gene (accession number AJ401156), which was identified by differential screening analysis. PD2 is the human homologue of the RNA polymerase II-associated factor 1 (hPaf1). In yeast, Paf1 is part of the transcription machinery, acting as a docking protein in between the complexes Rad6-Bre1, COMPASS-Dot1p, and the phosphorylated carboxyl terminal domain of the RNA polymerase II. As such, Paf1 is directly involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 43 publications
4
77
0
Order By: Relevance
“…We found that PD2/hPaf1, is overexpressed in the poorly differentiated pancreatic cancer cell line, Panc1. Further, the targeted overexpression of this gene in the NIH3T3 cell line led to transformation of the cells (Moniaux et al, 2006). These results suggest that the PD2/hPaf1 gene is a potential candidate of the oncogene family.…”
Section: Pd2/hpaf1 Is a New Candidate Oncogenementioning
confidence: 67%
See 1 more Smart Citation
“…We found that PD2/hPaf1, is overexpressed in the poorly differentiated pancreatic cancer cell line, Panc1. Further, the targeted overexpression of this gene in the NIH3T3 cell line led to transformation of the cells (Moniaux et al, 2006). These results suggest that the PD2/hPaf1 gene is a potential candidate of the oncogene family.…”
Section: Pd2/hpaf1 Is a New Candidate Oncogenementioning
confidence: 67%
“…These proteins are found to be associated with cancer progression either by overexpression or by downregulation during the course of the disease. We have reported a new candidate oncogene, pancreatic differentiation 2 (PD2)/hPaf1, a member of the hPAF complex, which is dysregulated in cancer (Moniaux et al, 2006). Another component of the hPAF complex with a known role in cancer is the hCdc73 subunit, also called parafibromin (Zhang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, PAF1 is amplified in pancreatic cancer, leading to the overexpression of Paf1 protein in poorly differentiated pancreatic cancer cells (Moniaux et al 2006). The overexpressed Paf1 regulates self-renewal and drug resistance of pancreatic and ovarian cancer stem cells (Vaz et al 2014).…”
mentioning
confidence: 99%
“…The yeast Paf1 complex is also known to participate in cell cycle control (Porter et al, 2002). Interestingly, it was reported that hPaf1 overexpression resulted in an enhancement of cell proliferation in opposition to the tumor suppressor activity of PF (Moniaux et al, 2006). Thus, overexpression of PF or hPaf1 affects the regulation of cell growth.…”
Section: Discussionmentioning
confidence: 99%